Desain dan Perancangan Shaker Table Vibration Testing Machine 3-Axis dengan Mechanical Exciter Slider Crank Mechanism - Yuda, Mohammad Wira; Abdi, Ferly Isnomo; Wulandari, Diah; Puspitasari, Dewi (Jurnal Rekayasa Mesin, 2025)
Vibration testing using a shaker table vibration tester aims to determine the dynamic characteristics and the structural endurance of a test object under vibrational or shock loads. The addition of motion axes (X, Y, Z) to the shaker table through the use of a connecting link rod-type exciter allows for greater displacement of the exciter, thereby expanding the variety of vibrational movements produced by the shaker table. This configuration enables more complex and varied testing conditions, leading to more comprehensive and representative test results. This research uses the Research and Development method by making a 3-axis shaker table vibration testing machine. Using a mechanical exciter slider crank with a connecting link rod as the mechanism, and varying the value of the connecting link rod installation distance on the deviation adjustment disk by 5, 10, 15, and 20 mm from the center point to vary the amplitude of the shaker table. The results of the machine function test obtained the vibration value of the frame when the machine operates with the test object at a deviation of 5 mm, which is 16.017 rms mm/s on the X axis, 17.237 rms mm/s on the Y axis, and 13.844 rms mm/s on the Z axis, while at a deviation of 10 mm the vibration value of the frame is 7.192 rms mm/s on the X axis, 28.224 rms mm/s on the Y axis, and 22.334 rms mm/s on the Z axis. From these data, it can be identified that the vibration of the frame falls into the unsafe category according to ISO 2372 standards.